Analysis Of The Implementation Of Financial Information Systems To Improve Financial Performance PT. Angkasa Pura Aviation - Aully Yullah; Nina Andriani; Fitriyani Panggabean (Yayasan Multidimensi Kreatif, 2025)
Year 2021 The financial information system at PT Angkasa Pura Aviasi currently uses the Mekari journal application. The use of this recording system is still relatively new and simple, so it becomes an obstacle in financial recording due to the need for adaptation to the new system. The identification of the problem is that the use of financial information systems using the mekari application system is still relatively new and there is no applicable SOP and financial performance using financial information systems cannot help optimally. The formulation of the problem is how to implement a financial information system to improve financial performance at PT Angkasa Pura Aviation? The purpose of this study to analyse the application of financial information systems to improve financial performance at PT Angkasa Pura Aviation. Qualitative descriptive research method. The data analysis technique used in this research is descriptive qualitative analysis, where the procedure is carried out by providing questionnaires and interviews to employees in the financial division who have used the financial information system, namely the mekari journal so that this is considered to improve financial performance. The results of the study are the application of financial information systems at PT Angkasa Pura Aviasi has had a significant positive impact on the company's financial performance. The system is able to control the activities of units in improving financial performance due to cost efficiency.